2010
DOI: 10.1074/jbc.m110.111120
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Plasma Membrane Expression of Dysferlin Mutants Is Attributed to Accelerated Endocytosis via a Syntaxin-4-associated Pathway

Abstract: Ferlins are an ancient family of C2 domain-containing proteins, with emerging roles in vesicular trafficking and human disease. Dysferlin mutations cause inherited muscular dystrophy, and dysferlin also shows abnormal plasma membrane expression in other forms of muscular dystrophy. We establish dysferlin as a shortlived (protein half-life ϳ4 -6 h) and transitory transmembrane protein (plasma membrane half-life ϳ3 h), with a propensity for rapid endocytosis when mutated, and an association with a syntaxin-4 end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 41 publications
4
39
0
Order By: Relevance
“…However, several studies have reported that deficiencies in dysferlin result in attenuated exocytosis and the accumulation of unfused vesicles at membrane lesions, suggesting a function in membrane fusion events that occur during repair of cell membrane wounds (9,12). In agreement with this, dysferlin has been reported to bind calcium and the cell membrane lipids phosphatidylserine and phosphatidylinositol bisphosphate and to co-localize with the SNARE protein syntaxin 4 (21)(22)(23)(24). Knockdown of dysferlin also results in a reduction in lysosome exocytosis and delayed release of acid sphingomyelinase, in agreement with dysferlin's proposed role in membrane fusion (11,13).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…However, several studies have reported that deficiencies in dysferlin result in attenuated exocytosis and the accumulation of unfused vesicles at membrane lesions, suggesting a function in membrane fusion events that occur during repair of cell membrane wounds (9,12). In agreement with this, dysferlin has been reported to bind calcium and the cell membrane lipids phosphatidylserine and phosphatidylinositol bisphosphate and to co-localize with the SNARE protein syntaxin 4 (21)(22)(23)(24). Knockdown of dysferlin also results in a reduction in lysosome exocytosis and delayed release of acid sphingomyelinase, in agreement with dysferlin's proposed role in membrane fusion (11,13).…”
supporting
confidence: 55%
“…reported to co-localize with syntaxin 4, a ubiquitously expressed SNARE protein that contributes to lysosomal exocytosis (21). To determine whether dysferlin interacts with syntaxin 4 as well as the cognate SNARE SNAP-23, dysferlin-immunoprecipitated samples from serum-starved differentiated C2C12 cells were probed by Western blot.…”
Section: Dysferlin Binds Syntaxin 4 and Snap-23-dysferlin Has Beenmentioning
confidence: 99%
“…Defects in many of these molecules are now also known to cause muscular dystrophies [52,[54][55][56]. Vesicle-mediated membrane resealing is clearly a dynamic process that involves both dysferlin and a complexity of molecules in order to patch the lesion.…”
Section: Pr Ospects and Overviews M D Grounds And T Shavlakadzementioning
confidence: 98%
“…Membrane resealing is a function conserved by most cells. Resealing via membrane vesicles is mediated by a mechanism resembling Ca 2þ -dependent exocytosis, which involves membrane fusion and key membrane proteins such as synaptotagmins and members of the ferlin family, with dysferlin being predominantly expressed in skeletal muscle [52][53][54].…”
Section: Sarcolemma Damage and Mechanisms For Membrane Resealingmentioning
confidence: 99%
“…Recent work has shown that dysferlin's plasma membrane localization is transitory; membrane anchorage never exceeds 3 hours, and the protein's half-life is only 5 hours. The syntaxin-4-associated endocytosis pathway plays a critical role in regulating this process (63).…”
Section: Introductionmentioning
confidence: 99%